2019
DOI: 10.1111/eve.13042
|View full text |Cite
|
Sign up to set email alerts
|

Standing repair of an articular dorsal medial oblique fracture of the proximal third metacarpal bone in a racing Standardbred

Abstract: Summary The third metacarpal bone (McIII) is a common site of long bone fractures in racehorses. However, articular fractures of the dorsomedial aspect of McIII are a rare location of such injuries. This report describes the successful standing surgical repair of an articular fracture of the dorso‐medial proximal McIII in a 4‐year‐old Standardbred racing mare using lag screw fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The temperament of the horse is paramount as it is imperative that the horse stands square and remains still throughout the duration of surgery (Compston & Payne, 2013;Lean & Ahern, 2020).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The temperament of the horse is paramount as it is imperative that the horse stands square and remains still throughout the duration of surgery (Compston & Payne, 2013;Lean & Ahern, 2020).…”
mentioning
confidence: 99%
“…Aßmann and colleagues utilised a combination of detomidine and morphine to provide sedation and analgesia in their case, the use of which is supported by other authors for standing surgery (Cillán‐García et al, 2020). Morphine was substituted for butorphanol by other authors (Jimenez‐Rihuete & O'Meara, 2022; Lean & Ahern, 2020; Russell & Maclean, 2006), but the analgesia afforded by butorphanol is short‐lived and has been shown to be inadequate for post‐castration analgesia (Love et al, 2009) and inferior to morphine in experimentally induced synovitis (Carregaro et al, 2014). Systematic review concluded that butorphanol has poor analgesic effects at doses used in clinical practice (Bowen et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation